Efektifitas Liveworksheet sebagai E-LKPD Berbasis Problem Based Learning Terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas X SMA Islam Al-Azhar 10 Pontianak - Riski Miranda, Kinana Dede; Firmansyah, Andang; Putri, Astrini Eka (Jurnal Ilmiah Wahana Pendidikan, 2025)
The implementation of the independent curriculum expects students to have critical thinking skills, this is also stated in the Pancasila student profile regarding critical reasoning. This is in line with the competencies needed in the 21st century related to 4C (critical thinking, creativity, collaborations, communication skills). However, students' critical thinking skills cannot be improved just like that, but must be trained continuously based on their level of education. Efforts that can be made by teachers are to innovate in learning activities, one of which is changing conventional LKPD into E-LKPD based on Problem Based Learning. This study was conducted with the aim of seeing the effectiveness of using liveworksheets as E-LKPD based on Problem Based Learning whether it is effective in improving the critical thinking skills of class X students. This study uses a quantitative method with an experimental research type. The collection technique uses observation sheets, test questions and documentation. Data analysis uses Normality Test, Homogeneity, N-gain Test, Percentage. The results of this study indicate (1) that based on the N-gain test, the experimental class obtained a result of 65.57 (quite effective) and the control class 41.76 (less effective); (2) that based on the results of observations in the experimental class regarding the use of E-LKPD based on Problem Based Learning which was assessed as very good for improving the critical thinking skills of class X students with observation results of 95. It can be concluded that the use of live worksheets as E-LKPD based on Problem Based Learning is quite effective for training the critical thinking skills of class X students with effectiveness results of 65.57 (quite effective).